2022
DOI: 10.1002/phar.2704
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of cefiderocol for off‐label treatment indications: A systematic review

Abstract: Purpose Cefiderocol is a siderophore cephalosporin recently approved by the United States Food and Drug Administration for the treatment of hospital‐ and ventilator‐acquired bacterial pneumonia and complicated urinary tract infections. However, there is potential for cefiderocol utility for a variety of other infections. The purpose of this systematic review was to identify literature examining the safety and efficacy of cefiderocol for off‐label indications. Methods The PRISMA guidelines were utilized for rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…10 However, cefiderocol is only FDA indicated for patients 18 years and older. 11 A recent study reported a 5.9% MDR resistance to TMP/SMX, 14.3% resistance to levofloxacin, and 31% resistance to ceftazidime in S. maltophilia bloodstream isolates from pediatric patients. 12 Use of combination therapy has been suggested for treatment of moderate T A B L E 1 Directed antibiotics for the treatment of S. maltophilia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 However, cefiderocol is only FDA indicated for patients 18 years and older. 11 A recent study reported a 5.9% MDR resistance to TMP/SMX, 14.3% resistance to levofloxacin, and 31% resistance to ceftazidime in S. maltophilia bloodstream isolates from pediatric patients. 12 Use of combination therapy has been suggested for treatment of moderate T A B L E 1 Directed antibiotics for the treatment of S. maltophilia.…”
Section: Discussionmentioning
confidence: 98%
“…Other choices for treatment include fluoroquinolones, ceftazidime, tetracyclines including tigecycline and minocycline (Table 1) while newer generation beta‐lactams like cefiderocol are reserved for MDR organisms 10 . However, cefiderocol is only FDA indicated for patients 18 years and older 11 . A recent study reported a 5.9% MDR resistance to TMP/SMX, 14.3% resistance to levofloxacin, and 31% resistance to ceftazidime in S. maltophilia bloodstream isolates from pediatric patients 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The debate about the most valuable option to use these new drugs, is still open, especially regarding the choice between monotherapy and combination therapy. Recommendations are not univocal for MDROs: clinical setting, pathogen isolation, infection source and disease’s severity assessment should guide the prescription [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen-day all-cause mortality, clinical cure, and microbiologic eradication were similar between treatment groups for participants infected with A. baumannii ; however, this group only comprised 16% of the study population, of which 66% of isolates were carbapenemase-resistant [ 111 ]. Cefiderocol has also been administrated as compassionate use in a limited number of case series with infections caused by XDR and PDR A. baumannii pathogens, resulting in a clinical success of 80% (20/25) [ 67 , 98 ]. Overall, the necessity of further studies to elucidate the true role of cefiderocol against A. baumannii infections in real life patients is needed.…”
Section: Pandrug-resistant Acinetobacter Baumanniimentioning
confidence: 99%